IN VITRO EVALUATION OF ANTIPLASMODIAL ACTIVITY OF EXTRACTS OF ACANTHOSPERMUM HISPIDUM DC (ASTERACEAE) AND FICUS THONNINGII BLUME (MORACEAE), TWO PLANTS USED IN TRADITIONAL MEDICINE IN THE REPUBLIC OF CONGO. - Koukouikila-Koussounda, Felix; Abena, Ange-Antoine; Nzoungani, August; Mombouli, Jean-Vivien; Ouamba, Jean-Maurille; Kunf, Jürgen; Ntoumi, Francine (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The aim of this study was to evaluate extracts from two medicinal plants, Acanthospermum hispidum and Ficus thonningii, used in traditional medicine in Congo Brazzaville, for in vitro antiplasmodial activities against two laboratory strains of Plasmodium falciparum: the chloroquine sensitive 3D7 and the chloroquine resistant Dd2. ELISA HRP2 assay was used to evaluate the in vitro inhibitory activity of the extracts alone or in combination with chloroquine. Cytotoxicity was assessed on human HeLa cell line and reflected by the selectivity index. Methanolic extract of Acanthospermum hispidum exhibited a strong and a moderate inhibitory activity on the growth of Dd2 and 3D7 at 2.8 µg/ml and 9.2 µg/ml concentrations respectively with a selectivity index >10. The combination of the most active extract (methanolic extract of Acanthospermum hispidum) with chloroquine showed a synergistic interaction on both strains. The good selectivity index of Acanthospermum hispidum on HeLa cells reflects the safety of this plant. Extracts from Ficus thonningii did not show any promising antiplasmodial activity on both 3D7 and Dd2. Except the methanolic extract which exhibited a slight antiplasmodial activity with inhibitory concentration and selectivity index corresponding to 9.61 µg/ml and 11.16 respectively. Methanolic extract of Acanthospermum hispidum exhibited moderate to high inhibitory activity on 3D7 and Dd2 laboratory strains and a synergistic antimalarial effect when combined with chloroquine. Ficus thonningii seems to have no antimalarial activity. Phytochemical analysis, in vivo investigations using animal models and later clinical trials in collaboration with traditional practitioners are necessary to clarify the potential antimalarial activity of both plants.